The making of international criminal justice a view from the bench : selected speeches - Meron, Theodor, 1930- (Oxford : Oxford University Press, 2011)
Bringing together Judge Meron's most important speeches in one volume, this text provides an insider's account of the development of international criminal law, humanitarian law, and human rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International criminal law; International criminal courts; Criminal jurisdiction; Judges